"Keep the Party Assured and the Youth [Not] Satisfied": The Communist Youth League and Chinese University Students. (March 2018) - Tsimonis, Konstantinos
The Communist Youth League (CYL) has attempted to engage and respond to student interests and demands by expanding its channels for participation and consultation and by deepening its involvement in the provision of welfare services. Based on qualitative and quantitative research conducted in five universities in Beijing and Zhejiang province, this article evaluates the league's engagement with its "constituency" on campus by bringing together the perspectives of both ordinary students and CYL cadres. Placing this case in a wider discussion of "authoritarian resilience" that seeks to understand the effectiveness of the Chinese regime's institutional sources of support, the article demonstrates that despite initiatives promoting responsiveness, students exhibit an even more cynical stance on both the league's newfound inclusivity and efficiency. CYL cadres occupy a weak position in the academic, generational, and political hierarchies on campus, a situation that compromises the league's potential for a renewed and more responsive engagement with students.